Cytotoxic Effects of Hibiscus surattensis L. Leaves Extracts on BSLT, MCF-7 and Hela Cells - Susanto, Yuliet - (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Hibiscus surattensis L. leaves have been known as a folk medicine. Several previous reports have shown several potential therapeutic effects, including antidiabetic, antibacterial, anti-diarrheal, analgesic, hepatoprotective, and antioxidant, but no toxicity study is similar to the current one. Therefore, it is necessary to investigate the cytotoxic effect of these commonly consumed medicinal leaves. This study aimed to investigate the cytotoxicity of Hibiscus surattensis L. leaves extract (HSL). The cytotoxic effect was determined through brine shrimp lethality bioassay (BSLT) and in vitro Presto Blue assay of MCF-7 and Hela cell. HSL extract was obtained by maceration using 96% ethanol. The BSLT results showed that the HSL has LC50 value of 224.814 μg/mL. MTT assay results showed the IC50 value of the HSL extract on MCF-7 cells was 1419.83 μg/mL, and Hela cells were 2050.50 μg/mL. Based on the LC50 value that has been analyzed against HSL extract shows an LC50 value of less than 1000 μg/mL which can be concluded while having potential cytotoxic activity against experimental animal larvae of A. salina Leach. The results of the cytotoxic test with Presto Blue assay on two cancer cells used showed that the HSL extract was not toxic.